Form-finding and optimization for free form grid structures supported by branching columns based on updated force density method. (October 2022) - Zhao, Zhongwei; Yu, Duo; Zhang, Tongrui; Gao, Hui
Abstract: The shape generation is one of the key problems in the research of grid structures and branching columns. The existing algorithms are only applicable to a single grid structure or branching column, but the interaction between grid structures and branching columns should be sufficiently considered in the design process. According to this research gap, a form-finding and intelligent optimization algorithm is presented for the grid structures with branching columns in this study. Firstly, the force density method is used to generate the shape of integral structures and the bending moment is removed completely. Since the members of branching columns are mainly subjected to axial compression, the buckling capacity can be the determining factor in the design. Secondly, the corresponding iterative optimization is utilized based on the form-finding analysis of branching columns by using the updated force density method (UFDM), which is combined with the Euler's buckling theory. The buckling capacity of branching columns can be maximized by using the UFDM. The intelligent section selecting algorithm is also added to the iterative optimization, which automatically selects the appropriate sectional size according to its internal force and material design strength. The applicability of the proposed algorithm is verified by analyzing numerical examples which come from actual projects.